"Floc" Story - Gaxiola, G.; Cuzon, G. (Facultad de Ciencias Biologicas, 2015)
What makes the effectiveness of the "floc" on growth of tropical shrimps and its reproductive capacities? The "floc" as called it 40 years ago also named "particulate" biomass came from the design of sludge from that purify the water on the one hand and consideration on the power mode of the other bivalves. When we come to these concepts we arrive at the concept of floc which produces a kind of shrimp "external rumen". What are the benefits that the animals retrieve? This article gives a review of chains of explanations in terms of environmental quality and the nutritional physiology of shrimp lead to what is now the most popular growing breeding model. This model represents a future opportunity to shrimp farming in the world by saving water, increased stocking densities and lower surfaces used and probably a freedom from direct use of the coastal zone. Will therefore be considered in this article nutritional aspects, changes in phytoplankton and microbial population and the interactions between nutrients, dissolved organic matter that give this chaotic culture medium and difficult aspect to control in any case and renderers very difficult to model. But some aspects of the shrimp physiology as its food/feed supplement behavior seem fixed in this farming system called "moulinettes" and recently resumed in the acronym "BFT biofloc" technology sometimes slightly obscuring the entire history of research in this area.